Precedent cultural nomens of culture in Ukrainian media - Shevchenko, Larysa (Current issues of Ukrainian linguistics: theory and practice, 2017)
The article is devoted to the investigation of one of the aspects of the precedent cultural nomens’ in the media text linguistic analysis. The author analyzes the thesis of the plurality of special interpretations of precedent phenomena conditioned by their nature. Also the attention is paid to the textual interpretation of the represented in the text of Yuri Makarov Taras Shevchenko name which is precedent for the mass cultural consciousness of Ukrainians.
Keywords: precedent cultural nomens, author's interpretation, mass cultural consciousness, media text, structural antithesis.